2014
DOI: 10.1021/am405601g
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Triangular Pd Rod Nanostructures and Their Electrocatalytic and SERS Activities

Abstract: We report a simple one-step electrodeposition of triangular Pd rod nanostructures on clean Au substrates without additives. Scanning electron microscopy, transmission electron microscopy, and electrochemical techniques were utilized to characterize the structural features of the triangular Pd rod nanostructures. The regulation of the electrodeposition rate by optimizing the electrolyte concentration and applied potential was critical for the anisotropic growth of Pd in the vertical direction. The triangular Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 36 publications
(52 reference statements)
0
37
0
Order By: Relevance
“…In addition to chemically synthesised cubic palladium nanoparticles, triangular Pd rods have been prepared by electrochemical deposition [11]. These particles had mostly Pd(111) planes on the surface and also some Pd(100) and displayed a higher electrocatalytic activity towards the ORR and methanol oxidation as compared to polycrystalline Pd surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to chemically synthesised cubic palladium nanoparticles, triangular Pd rods have been prepared by electrochemical deposition [11]. These particles had mostly Pd(111) planes on the surface and also some Pd(100) and displayed a higher electrocatalytic activity towards the ORR and methanol oxidation as compared to polycrystalline Pd surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…During the electrodeposition process, the electrode potentials applied at substrate electrodes play an important role in determining the electrodeposited metal structures. We showed that different Pd nanostructures were obtained depending on the applied electrodeposition potential, whereas other electrochemical variables, such as precursor concentrations and electrolyte compositions, have little influence on the resulting metal nanostructures .…”
Section: Introductionmentioning
confidence: 96%
“…And the presence of precursor concentration gradient layer near the electrode surface can significantly influence the growth orientation of metal nanostructures. Many works have been done to prepare metal nanostructures for SERS-active substrates by electrochemical deposition, such as silver nanosheets [17] , triangular Pd rod nanostructures [18] , Au nanoparticles [19] and thin films [20] . On nanoporous gold, Yang et al prepared silver nanoparticles by electroless deposition and observed 10 4 times SERS improvement compared to the as-prepared NPG films, which is attributed to the abundant Raman-active nanogaps constructed adjacent nanoparticles and also by the NPG ligaments and adhered nanoparticles [21] .…”
Section: Introductionmentioning
confidence: 99%